TRANSFORMATION OF VOCATIONAL TRAINING IN HOTEL AND CATERING MANAGEMENT PROGRAMS TO MEET HIGH INCOME COMMUNITY IN GLOBAL PERSPECTIVE - Zakaria, Mohd Amin Bin; Bintatan, Noor Afizah; Hussein, Fatimah Binti (Universitas Pendidikan Indonesia, 2015)
The Hotel and Catering Management program has gone trough years in Malaysian’s conventional education. The pioneer of this program has been established at Institut Teknologi MARA in 1967 started from Certificate of Catering Services to Diploma in Hotel and Tourism Management. From its name School of Hotel and Catering Management, in 1991 it is called Faculty of Hotel and Tourism Management. The faculty focuses in line with the country aspiration to produce graduates and professionals in the field of hospitality. Meanwhile, in secondary schools have made catering courses as an elective in Living Skill and vocational school has long made Certificate of Catering courses to students. In 1998, Politeknik Johor Bahru has opened first certificate and diploma programs in Hotel and Catering Management to produce workers in respective hospitality establishments available through Malaysia. It is considered the second public institution for hotel and catering programs in Malaysia. However, reports from the Traces Study and Alumni Department in Politeknik Johor Bahru had shown that less than 65 percent of students interested to work in the same discipline and the rest of them divided in all fields in workforce. This trend has been prevailing for years in the job market without any action been taken to address this problem. This paper is to look and to analyze the reason why students do not choose their first jobs associated with the areas that they have been studied. After finding out the cause of the problems, number of recommendations to the formation of a new curriculum on Hospitality Education should be made to fit the current trend and market. Therefore, the shortage of energy resources and dependency on external energy could be reduced. The new curriculum is hoping to be able in developing communities with high income toward Malaysian’s vision to be a developed country in 2020.